Metabolic Studies on BMS-200475, a New Antiviral Compound Active against Hepatitis B Virus - Yamanaka, Gregory (American Society for Microbiology, 1999)
BMS-200475 was recently shown to have potent antiviral activity against hepatitis B virus (50% effective concentration = 3.7 nM; 50% cytotoxic concentration = 30 μM). In metabolic studies in both HepG2 and hepatitis B virus-transfected 2.2.15 human hepatoma cell lines, the metabolism was similar, the primary products being the di- and triphosphates. The accumulation of triphosphate was rapid and detectable down to a 5 nM concentration of added drug. When cells were labeled at 25 μM, the intracellular triphosphate concentration attained 30 pmol/10(6) cells (∼30 μM). The intracellular half-life of the triphosphate was about 15 h. Compared with five other nucleoside analogs of medical interest (lamivudine, penciclovir, ganciclovir, acyclovir, and lobucavir), BMS-200475 was most efficiently phosphorylated to the triphosphate in HepG2 cells.